The effect of fiscal variables on economic growth in Asian economies: a dynamic panel data analysis - Abdullah, Hussin; Habibullah, Muzafar Shah; Baharumshah, Ahmad Zubaidi (Canadian Center of Science and Education, 2009)
This paper investigates the effect of relationship between fiscal variables and economic growth in Asian economies using a generalized method of moments (GMM) method as a dynamic panel data analysis over the 1985 – 2001 periods. These data contain a number of time invariant and time varying variables, where the time varying variables are averaged over four year It examines two different channels through which fiscal policy can affect long run economic growth in Asia. The first channel is when components and aggregate government expenditure affects the real per capita GDP and the second channel is when the components and aggregate of other fiscal variables affects the real per capita GDP. The dynamic panel data result especially GMM-SYS establishes a long run relationship between fiscal policy and economic growth. We find positive and statistically significant impact of health and education expenditure, aggregate of government expenditure and aggregate of other fiscal variables on real per capita GDP. Furthermore, we find that the defence expenditure, distortionary taxation and budget balance are significantly and negatively related to real per capita GDP.